Three-point functions in Aharony-Bergman-Jafferis-Maldacena theory and integrable boundary states - Jun-Bao Wu; Peihe Yang (Journal of High Energy Physics)
Abstract We investigate the correlators of three single-trace operators in Aharony-Bergman-Jafferis-Maldacena (ABJM) theory from the perspective of integrable boundary states. Specifically, we focus on scenarios where two operators are 1/3-BPS and the entire correlation function is considered within the twisted-translated frame. The correlator can be expressed as the overlap between a boundary state and a Bethe state. It is found that the boundary state formed by the two 1/3-BPS operators is integrable when the number of Wick contractions between the non-BPS operator and one of the 1/3-BPS operators is 0 or 1. We compute the overlaps for the proven integrable cases utilizing the symmetries and the coordinate Bethe ansatz.